Investigation of traffic impact on RDCLRP. (1st January 2014) - Fatima, Mehajabeen; Gupta, Roopam; Bandhopadhyay, T.K.
Routing fails frequently owing to scarce energy resources and movement of nodes in mobile adhoc network (MANET). This hampers the data flow continuity and limits the performance of routing protocol. Maintaining an uninterrupted flow of traffic is the key challenge in the design of efficient routing protocol. An algorithm RDCLRP (route discovery using cross layer routing protocol) is proposed to reduce discontinuity of data flow. An on-demand route is discovered in advance before route failure to avoid route instability. The modifications are made to the AODV protocol's route maintenance mechanism in order to develop RDCLRP. Three variants of proposed work are developed and their results are discussed. Performance of proposed algorithm is investigated for change in traffic. Proposed algorithm illustrates that the data flow discontinuity rate is reduced by 90% over AODV.